Sistem Pakar Diagnosa Penyalahgunaan Zat Adiktif Pada Kantor Badan Narkotika Nasional (BNN) Kota Palu - Ika Fatmawati; Dinny Daniela Amping (Jurnal Elektronik Sistem Informasi dan Komputer, 2026)
Substance abuse remains widespread in Indonesia. According to medical doctors and experts, this condition is caused by a lack of public outreach and awareness regarding the dangers of drug abuse, as well as limited knowledge about addictive substances, including their side effects and harmful impacts. With advances in technology that support various aspects of modern human life, new opportunities arise to develop systems in the form of programs or applications that can assist individuals in independently identifying and diagnosing the symptoms and types of addictive substances used by abusers. An expert system application is an information system that can help the public find solutions to problems without having to consult directly with specialist experts. The purpose of this research is to develop a website-based expert system application that can assist the public in diagnosing substance abuse. This study employs the forward chaining inference method, which is used when facts are not associated with elements of uncertainty in decision making. An expert system that applies the forward chaining method can be implemented in a website-based application.